Single dose oral zinc as adjuvant therapy in children admitted with severe pneumonia: A randomized, placebo-controlled study - Basavraj, G V; Nijaguna, N; Gembeeran, Raja; Sanjeeva, G N (Indian Journal of Child Health, 2016)
Background: Childhood pneumonia is one of the major causes of under-five mortality in developing countries. Any interventions which can reduce the mortality and morbidity of pneumonia are of great importance. Adjuvant zinc therapy is one such intervention studied in various parts of the world with inconclusive results. Objective: We aim to study the impact of a single dose of zinc therapy on the outcome of childhood severe pneumonia. Material and Methods: Randomized, placebo-controlled study of young children between2 and 24 months was conducted to study the impact of single dose zinc administration on time to resolution of severe pneumonia. The subjects were assigned two groups, zinc group and non-zinc group, by stratified randomization. The zinc group received unlabeled oral zinc syrup 20 mg of elemental zinc as single dose for children >6 months of age and 10 mg of elemental zinc as single dose for children